Preliminary study: kinetics of oil extraction from citronella grass by ohmic heated hydro distillation - Che Man, Hasfalina; Hamzah, Muhammad Hazwan; Jamaludin, Hishamuddin; Zainal Abidin, Zurina (Elsevier, 2012)
Citronella grass is native to India and Sri Lanka; which the plant found growing wild in most tropical Asian countries including Malaysia. In Malaysia, it is planted in the kitchen gardens. The oil has been used in soap, perfumery, cosmetics, flavouring industries and health purposes. The aim of this study is to know and verify the kinetics and mechanism of ohmic heated hydro distillation of citronella grass based on a second order model. In this study, ohmic heated hydro distillation is used to extract essential oils from citronella grass. The extraction was carried out in eight extraction cycles of 15 minutes to 3 hours. The initial extraction rate, the saturated extraction capacity and the rate constant of extraction were calculated using the model. Kinetics of oil extraction from citronella grass by ohmic heated hydro distillation proved that the extraction process was based on the second order extraction model as the extraction experimentally done in two stages. The initial extraction rate, h, was 0.49653 gL-1 min-1; the extraction capacity, Cs, was 3.74251 gL-1; the second order extraction constant, k, was 0.03545 Lg-1min-1 and coefficient of determination, R2 was 0.99419.